A Riet River retrospective - Humphreys, A. J. B. (Southern African Humanities, 2021)
There is, along the banks of the Riet River, on the border between the Free State and adjacent part of the Northern Cape, a series of stone-built settlements which present evidence suggests were built by Bushmen-turned-pastoralists during the period, roughly, from the eleventh to nineteenth centuries. This paper draws, in part, on this existing evidence in an attempt to understand the reason for the very restricted distribution of these so-called Type R settlements. It is suggested that a behavioural ecology approach best explains the emergence and distribution of these enigmatic stone structures. To cite this article: Humphreys, A.J.B. 2009. A Riet River retrospective. Southern African Humanities 21: 157-175.